2007
DOI: 10.1177/1087057107302676
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tau Stem Loop RNA Stabilizers

Abstract: Alternative splicing of tau exon 10 produces tau isoforms with either 3 (3R) or 4 (4R) repeated microtubule-binding domains. Increased ratios of 4R to 3R tau expression, above the physiological 1:1, leads to neurofibrillary tangles and causes neurodegenerative disease. An RNA stem loop structure plays a significant role in determining the ratio, with decreasing stability correlating with an increase in 4R tau mRNA expression. Recent studies have shown that aminoglycosides are able to bind and stabilize the tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Stabilization of the RNA’s structure restores normal splicing patterns (Donahue et al, 2006) (Figure 7). A high throughput, FRET-based screen identified that the intercalator mitoxantrone (MTX, LDN-13978) stabilizes the mutated MAPT hairpin (Donahue et al, 2007). Importantly, mere intercalating ability is not sufficient for stabilization (Donahue et al, 2007).…”
Section: Leveraging Rna Structure To Design Chemical Probes Of Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stabilization of the RNA’s structure restores normal splicing patterns (Donahue et al, 2006) (Figure 7). A high throughput, FRET-based screen identified that the intercalator mitoxantrone (MTX, LDN-13978) stabilizes the mutated MAPT hairpin (Donahue et al, 2007). Importantly, mere intercalating ability is not sufficient for stabilization (Donahue et al, 2007).…”
Section: Leveraging Rna Structure To Design Chemical Probes Of Functionmentioning
confidence: 99%
“…A high throughput, FRET-based screen identified that the intercalator mitoxantrone (MTX, LDN-13978) stabilizes the mutated MAPT hairpin (Donahue et al, 2007). Importantly, mere intercalating ability is not sufficient for stabilization (Donahue et al, 2007). A structural study of MTX complexed with the MAPT hairpin by NMR spectroscopy revealed that MTX binds the bulge region of the stem-loop (Zheng et al, 2009).…”
Section: Leveraging Rna Structure To Design Chemical Probes Of Functionmentioning
confidence: 99%
“…Having validated the tau stem-loop RNA as a significant regulatory element in controlling tau mRNA splicing, we designed a high-throughput screen to identify small molecule ligands of the stem-loop RNA and developed other assays to validate the results of this screen [38]. Such compounds should stabilize the stem-loop and lower the 4R-to-3R ratio (i.e., do the opposite of disease-causing mutations).…”
Section: Tau Mrnamentioning
confidence: 99%
“…We previously reported a high-throughput screen to identify small, organic molecules that bind and stabilize the tau RNA hairpin and discovered mitoxantrone (MTX) as such a ligand [15]. Elucidation of the structure of MTX bound to the tau RNA hairpin by NMR revealed that the anthracene-dione ring system intercalates between two G–C base pairs, adjacent to an unpaired adenosine and close to the base of the hairpin (Fig.…”
Section: Introductionmentioning
confidence: 99%